Integrating young male refugees: initial evidence from an inclusive soccer project - Martin Lange; Friedhelm Pfeiffer; Gerard J. van den Berg (Journal for Labour Market Research, 2017)
This study analyses data collected among a group of young male refugees who participated in a randomised experiment. Refugees were randomly assigned to a soccer project aimed at facilitating social and labour market integration or to a control group. We evaluate the randomisation process, discuss the design and implementation of the survey and summarize the main findings of the survey by focusing on labour market activity, pre-migration characteristics, and the monetary costs of the escape. In addition, we provide a preliminary outlook on the effectiveness of the programme.
Keywords: C93; F22; J15; J24; 330; Refugees; Randomised experiment; Labour market integration